10 Evidence that altered redox status results in KCa3.1 channel reduced endothelial cell surface expression. (1st December 2018) - Fraser, Paul; Bani Khalaf, Anas; Mann, Giovanni; Smith, Matthew; Clough, Geraldine
Abstract: Introduction: Endothelial derived hyperpolarization (EDH) is an important path to vasodilatation especially in small arteries, and is more important in women and the elderly. Our previous work has shown that this becomes impaired in mice that had experienced a high fat diet during gestation up to weaning, with concomitant reduction in endothelial surface KCa3.1 expression. 1 We have tested the idea that altered redox status affects the location of KCa3.1 in human dermal microvascular endothelial cells (HDMECs). Methods: HDMECs were obtained from PromoCell (Heidelberg, Germany) and cultured in MV2 growth medium containing 1% penicillin-streptomycin in 5% O2, 5% CO2 at 37°C to passage 6 and 7 in the SCI-tive Physiological Oxygen Workstation from Baker Ruskinn (Maine, USA) for at least 5 days before experiments. The cells were plated on fibronectin (10 µg.ml -1 ) coated 8 well micro-slides (Ibidi, Martinsried, Germany) and incubated for 48 hour, treated with PBS or H2 O2 100 µM in PBS for 10 min., and fixed with 4% formalin. Immunofluorescence was performed by incubating with anti-KCa3.1 mouse monoclonal antibody (AL-051 Alomone, Israel) at 4°C overnight, with half of the wells being treated with 2% Triton-X to permeablize the cells. The Alexa 488 labelled anti-mouse antibody for 1 hour and Texas Red Lycopersicon Esculentum Lectin (to stain the cell surface) for 20 min, were applied to the cells at room temperature and finally the DAPI nuclear stain was applied for 3 min. The cells were examined using a x60 1.3 NA oil-immersion objective and images captured via a Hamamatsu RG3 camera into a computer. Using ImageHopper software and computer-driven focussing device (Prior Instruments, UK) we took 10 serial images of KCa3.1at 1.0 µm intervals, which were integrated using Image J. These images were analysed for the fractional area of an endothelial cell occupied by KCa3.1, defined as bright spots between 1 to 4 µm diameter in the relevant fluorescence channel. Results: The density of channels on the surface, defined as the integrated image of non-permeablized KCa3.1 channels, was 9.5±0.68 µm -2 × 10 3 (mean ±sem), while in the permeablized cells the density within the whole cell area was 13.9±1.89 µm -2 × 10 3 (p<0.05, 't' test, 4 experiments with 20 cells per experimental group) indicating that about 70% of the channels normally reside on the cell surface. Treatment with H2 O2 had little effect on the total cell density (reduced to 12.3±1.56), but reduced the surface density to 5.25±0.47 (p<0.01) i.e. reduced to 43%. Conclusion: Thus even a brief exposure to oxygen stress will result in the diminution of KCa3.1 on endothelial surface, and this may have implications for the ability of arterioles to dilate. Reference: Stead R, et al . J Hypertens2016;34:452–63.